Efeitos do exercício aeróbio pré-prandial sobre a glicemia de indivíduos jovens - Seganfredo, Leonardo (2021)
Physical exercise is effective in reducing blood glucose when performed after meals, but there is no consensus in the literature regarding its effects on blood glucose when performed before a meal. Objective: This study aims to verify the effect of previous aerobic exercise on the glycemic curve through dextrose ingestion in young individuals. Method: There were five non-consecutive visits to the laboratory with a minimum interval of 72 hours. The first for the initial screening of the participant, and the others for carrying out the conditions "exercise" and "control" with "dextrose" and "placebo" (randomized). The physical exercise session was a moderate-intensity walk/run (60 to 75% of the reserve heart rate), and the control session was carried out keeping the participant seated. The protocol consisted of 20 minutes of pre-exercise/control rest, 20 minutes of physical exercise/control, and 75 minutes of post-exercise recovery. The dextrose/placebo solution was ingested at 15 minutes of recovery. Blood glucose was measured at the end of rest, exercise and every 15 minutes during recovery. Results: Resting blood glucose did not differ between the four experimental conditions (p=0.089) with a mean of 90.85 ± 20.75 mg/dL. Physical exercise was effective in reducing blood glucose, as there was a percentage reduction in blood glucose of greater magnitude (p=0.03) at the end of exercise compared to the similar period of control without exercise. However, there was no statistical difference in the area under the curve (p>0.05) Conclusion: Physical exercise performed for only 20 minutes was able to reduce blood glucose, however, there was no slowdown in the blood glucose curve upon ingestion of dextrose in the period following the exercise.